Penggunaan Alat Peraga Untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Kelas IV SD Riyadlul Muta’allimin - Tobroni, Tobroni; Fatkhiyani, Kiki; Khasanah, Uswatun (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research is aimed to increase student motivation and learning outcomes by using teaching aids for fourth grade students of SD Riyadlul Muta'allimin Tenajar, Kertasemaya District, Indramayu Regency for the 2020/2021 academic year on flat-building material. This is motivated by a problem of motivation in students as evidenced by students' lack of focus in learning, such as joking, daydreaming and playing when learning takes place. lack of encouragement from the surrounding environment and not diligent in learning and low student learning outcomes. This research was conducted using a classroom action research method, it can be explained that the results of increasing pre-cycle motivation are not good with a monotonous learning process without using teaching aids and student learning outcomes from pre-cycle are still low or have not reached the KKM. Only 7 students reached the KKM. In cycle 1, the use of teaching aids has been applied in the learning process to increase motivation by 67.7% with good criteria and in cycle 2 it reaches 87.9% with very good criteria. Meanwhile, student learning outcomes after the use of teaching aids were applied to the learning process in cycle 1 achieved completeness of 64.3% or as many as 18 students. In cycle 2 it increased to 89.3% as many as 25 students who completed exceeding the success indicator by 80%. Based on these results, it can be said that classroom action research with use of teaching aids can increase the motivation and learning outcomes of fourth grade students of SD Riyadlul Muta'allimin.